1999
DOI: 10.1128/jb.181.13.4118-4124.1999
|View full text |Cite
|
Sign up to set email alerts
|

The pvc Gene Cluster of Pseudomonas aeruginosa : Role in Synthesis of the Pyoverdine Chromophore and Regulation by PtxR and PvdS

Abstract: A putative operon of four genes implicated in the synthesis of the chromophore moiety of the Pseudomonas aeruginosasiderophore pyoverdine, dubbed pvcABCD (wherepvc stands for pyoverdine chromophore), was cloned and sequenced. Mutational inactivation of the pvc genes abrogated pyoverdine biosynthesis, consistent with their involvement in the biosynthesis of this siderophore. pvcABCD expression was negatively regulated by iron and positively regulated by both PvdS, the alternate sigma factor required for pyoverd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 45 publications
1
63
0
1
Order By: Relevance
“…PvcA and PvcB are required for synthesis of pyoverdine chromophore, they serve as signalling molecules controlling gene expression inside the cell and have been reported to be induced in biofilm and regulated by iron Significantly differentially regulated genes are marked by an asterisk. **P < 0.001. concentrations available (Stintzi et al, 1999;Hindre et al, 2008; Table 3). Thus the general transcriptional response of L. pneumophila to oxidative stress leads to the induction of two alkyl-peroxidases and iron related genes.…”
Section: Kaic Influences the Expression Of The Alkyl-peroxidases Ahpcmentioning
confidence: 99%
“…PvcA and PvcB are required for synthesis of pyoverdine chromophore, they serve as signalling molecules controlling gene expression inside the cell and have been reported to be induced in biofilm and regulated by iron Significantly differentially regulated genes are marked by an asterisk. **P < 0.001. concentrations available (Stintzi et al, 1999;Hindre et al, 2008; Table 3). Thus the general transcriptional response of L. pneumophila to oxidative stress leads to the induction of two alkyl-peroxidases and iron related genes.…”
Section: Kaic Influences the Expression Of The Alkyl-peroxidases Ahpcmentioning
confidence: 99%
“…It has been demonstrated that pyoverdine is synthesized by a non-ribosomal mechanism, and is assembled by a series of enzymes including the peptide synthetase PvdD [3]. In P. aeruginosa PAO chromosome, genes implicated in synthesis of pyoverdine have been mapped at regions 23 and 47 min [5], and recently the pvc cluster localized at 66^70 min was described [6,7]. We present evidence that three open reading frames (ORFs) upstream of pvdD, called pvdIJK, form a putative cluster with pvdD and are implicated in pyoverdine biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The pyoverdine-reduced phenotype of the ferrochelatase vhemH mutant suggests that PPIX accumulation, or lack of heme, or both, are directly responsible for the inhibition of siderophore production. The genes for the biosynthesis of the pyoverdine chromophore have been identi¢ed [7,8]. They include one oxygen- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent molecular mass of the ferrochelatase from P. £uorescens was estimated by comparison with the bench mark protein ladder (Life Technologies). ase and one hydroxylase present in the cytoplasm, and one di-heme cytochrome c4 in the periplasm [8]. A shortage of heme could therefore cause a slow-down of the chromophore biosynthesis [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation